Uncovering the Roots of Paternal Negligence in Child Support After Divorce in Pariangan District - Raflis, Aullya; Yunarti, Sri; Kasmidin, Kasmidin (Jurnal El-Thawalib, 2025)
Child support is a right guaranteed by Islamic law and positive Indonesian law, but in practice, it is often ignored by fathers after the breakup of a marriage. This study aims to uncover the root causes of fathers' negligence in providing child support after divorce in Pariangan District. This type of research is field-based and qualitative. Primary data sources are directly from ex-wives who have divorced and experienced problems in receiving child support, as well as religious leaders, traditional leaders, and the Office of Religious Affairs (KUA) in Pariangan District. Secondary data sources include fiqh books, Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law (KHI), journals, and scientific articles. Data obtained through observation, interviews, and documentation from religious leaders and local KUA officials. Data analysis techniques: Qualitative Descriptive. The results of this study indicate that the obligation to provide child support in Pariangan District does not have standard guidelines from the court, so that fathers often provide support according to their wishes and not according to the child's needs. Economic factors cause paternal neglect, a lack of understanding that children are their responsibility, the influence of Minangkabau customs, women's ignorance in court proceedings, fathers who remarry, and a lack of trust from ex-husbands in their wives. In Minangkabau customs, especially in Pariangan, mothers play a role in providing for their nephews, as the saying goes: "Anak dipangku, kamanakan dibimbing" (child in the lap, kamanakan dibimbing).